In situ characterization of AA1050 recrystallization kinetics using high temperature nanoindentation testing. (15th August 2018) - Baral, Paul; Laurent-Brocq, Mathilde; Guillonneau, Gaylord; Bergheau, Jean-Michel; Loubet, Jean-Luc; Kermouche, Guillaume
Abstract: Static recrystallization kinetics, at 300 °C, of a hot rolled commercial purity aluminum alloy AA1050 has been investigated using high temperature nanoindentation. Annealing treatments were achieved inside a nanoindentation device to measure corresponding hot nanohardness versus time. Clear evidences of recrystallization phenomenon were deduced from both hardness decrease and pop-in events on load-displacement curves. The recrystallized fraction for increasing annealing time was compared to conventional post mortem characterizations – i.e. EBSD and Vickers hardness. A good agreement was found between in situ and post mortem characterization methods. High temperature nanoindentation is proved to be a powerful tool for fast characterization of materials' recrystallization kinetics. Graphical Abstract: Highlights: Hot nanoindentation as an in situ measurement technique of the recrystallization kinetics. The decrease in hot nanohardness is consistent with EBSD microstructure investigations and post mortem hardness measurements. Pop-in events are clear evidences of the recrystallization phenomenon for the studied Aluminum alloy. Hot nanoindentation allows for fast and economical characterization of microstructure evolutions during heat treatments. It opens a new way to investigate in situ recrystallization mechanisms at the micron scale.